The Microbe-Free Plant: Fact or Artifact? - Partida-Martinez, Laila P. P.; Heil, Martin (Frontiers in Plant Science, 2011)
Plant-microbe interactions are ubiquitous. Plants are often colonized by pathogens but even more commonly engaged in neutral or mutualistic interactions with microbes: below-ground microbial plant associates are mycorrhizal fungi, Rhizobia and rhizosphere bacteria, above-ground plant parts are colonized by bacterial and fungal endophytes and by microbes in the phyllosphere. We emphasize here that a completely microbe-free plant is an exotic exception rather than the biologically relevant rule. The complex interplay of such microbial communities with the host plant affects plant nutrition, growth rate, resistance to biotic and abiotic stress, and plant survival and distribution. The mechanisms involved reach from nutrient acquisition, the production of plant hormones or direct antibiosis to effects on host resistance genes or interactions at higher trophic levels. Plant-associated microbes are heterotrophic and cause costs to their host plant, whereas the benefits depend on the environment. Thus, the outcome of the interaction is highly context-dependent. Considering the microbe-free plant as the ‘normal’ or control stage significantly impairs research into important phenomena such as (1) phenotypic and epigenetic plasticity, (2) the ‘normal’ ecological outcome of a given interaction and (3) the evolution of plants. For the future, we suggest cultivation-independent screening methods using direct PCR from plant tissue of more than one fungal and bacterial gene to collect data on the true microbial diversity in wild plants. The patterns found could be correlated to host species and environmental conditions, in order to formulate testable hypotheses on the biological roles of plant endophytes in nature. Experimental approaches should compare different host-endophyte combinations under various environmental conditions and study at the genetic, transcriptional and physiological level the parameters that shift the interaction along the mutualism-parasitism continuum.